Assessment of Cereals for Fungal Contaminants and Presence of Aflatoxins from Two Major Markets in Kaduna Metropolis - Abdulrahman, Idris; Danbaba, Amina Aliyu; Uba, Garba (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Aflatoxins are mycotoxins produced by fungi of the genus Aspergillus that contaminate food products such as cereals leading to serious health and economic consequences. In order to assess the level of fungal contaminants and the presence of aflatoxins in such products, five (5) different cereal samples comprising of rice, maize, millet, wheat and sorghum were purchased each from two major markets within Kaduna metropolis. The samples were assessed for fungal contaminants using ten-fold serial dilution and cultured appropriate dilutions using pour-plate technique. Aflatoxins were detected using Enzyme-linked Immunosorbent Assay (ELISA). The results obtained revealed viable fungal counts ranging from 3 x 102 to 3.2 x 103 cfu/g. The fungal contaminants identified from the samples include Aspergillus flavus, Aspergillus niger, and Aspergillus fumigatus. The aflatoxins detected from the samples were within the range of 0.3 to 0.6 part per billion (ppb) which is less than the maximum value (10ppb) recommended by regulatory agencies such as NAFDAC. This indicates that the level of aflatoxin in the samples has insignificant risks to consumers. However, the fungal contamination is an indication of high-level contamination of the cereals, the key producers of aflatoxins. The contamination of such products by fungi should be a source of worry and necessitates the need for proper personal and environmental hygiene in the processing of cereals.